Do lagomorphs play a relay role in the evolution of the Trichostrongylina nematodes? - Audebert F.; Durette-Desset M.C. (Parasite, 2007)
In order to confirm or refute the relay role of lagomorphs in the evolution of the Trichostrongylina (Nematoda), the following points were studied by summarizing previous works on the subject: the chronology of the life cycles (27 conducted in natural hosts, lagomorphs, ruminants or arvicolin rodents; 14 in experimental hosts); the parasitic phase in the experimental host and the adaptation involved; the migration of the parasites into the tissues of the host; the morphogenesis of larval stages and molecular phylogeny. These data confirm, in their entirety, that lagomorphs may be considered as “relay” hosts in the evolution of the Trichostrongylina.